JAK Inhibition Differentially Affects NK Cell and ILC1 Homeostasis - Vian, Laura; Le, Mimi T.; Gazaniga, Nathalia; Kieltyka, Jacqueline; Liu, Christine; Pietropaolo, Giuseppe; Dell'Orso, Stefania; Brooks, Stephen R.; Furumoto, Yasuko; Thomas, Craig J.; O'Shea, John J.; Sciumè, Giuseppe; et al. (Frontiers in Immunology, 2019)
Janus kinase (JAK) inhibitors are widely used in the treatment of multiple autoimmune and inflammatory diseases. Immunologic and transcriptomic profiling have revealed major alterations on natural killer (NK) cell homeostasis associated with JAK inhibitions, while information on other innate lymphoid cells (ILCs) is still lacking. Herein, we observed that, in mice, the homeostatic pool of liver ILC1 was less affected by JAK inhibitors compared to the pool of NK cells present in the liver, spleen and bone marrow. JAK inhibition had overlapping effects on the transcriptome of both subsets, mainly affecting genes regulating cell cycle and apoptosis. However, the differential impact of JAK inhibition was linked to the high levels of the antiapoptotic gene Bcl2 expressed by ILC1. Our findings provide mechanistic explanations for the effects of JAK inhibitors on NK cells and ILC1 which could be of major clinically relevance.